2016
DOI: 10.1039/c6cc05460a
|View full text |Cite
|
Sign up to set email alerts
|

Highly dynamic metal exchange in anthrax lethal factor involves the occupation of an inhibitory metal binding site

Abstract: Metal exchange is a common strategy to replace the zinc ion of many zinc proteins with other transition metals amenable to spectroscopic investigations. We here demonstrate that in anthrax lethal factor (and likely other zinc proteases), metal exchange is a fast process, and involves the occupation of an inhibitory metal site by the incoming ion prior to the release of zinc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The binding site of the catalytic Zn ion in DPP III is very similar to those in thermolysin (TML), carboxypeptidase A (CA), and anthrax lethal factor, i.e., in all of these, the zinc ion is coordinated by two histidines and a glutamate. In addition, all of these proteins can bind other divalent ions, such as Cu, Co, and Mn, excess metal ions inhibit their enzyme activity, and an inhibitory binding site has been identified [ 20 , 22 , 23 ]. It has also been shown that the binding of zinc and other metals in excess can lead to the inhibition of DPP III in humans, rats, and microorganisms [ 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The binding site of the catalytic Zn ion in DPP III is very similar to those in thermolysin (TML), carboxypeptidase A (CA), and anthrax lethal factor, i.e., in all of these, the zinc ion is coordinated by two histidines and a glutamate. In addition, all of these proteins can bind other divalent ions, such as Cu, Co, and Mn, excess metal ions inhibit their enzyme activity, and an inhibitory binding site has been identified [ 20 , 22 , 23 ]. It has also been shown that the binding of zinc and other metals in excess can lead to the inhibition of DPP III in humans, rats, and microorganisms [ 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the binding of zinc and other metals in excess can lead to the inhibition of DPP III in humans, rats, and microorganisms [ 9 , 10 , 11 ]. All of these findings indicate that metal ions can bind not only at the catalytic site of DPP III, but also at an additional, so-called inhibitory binding site [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chelators such as 1,10-phenanthroline (OP) and dipicolinic acid (DPA) have been found to follow an A-type mechanism with a variety of metalloenzymes . In contrast, larger and more sterically demanding chelators such as ethylenediaminetetraacetic acid (EDTA) are generally considered to act via a D-type mechanism, ,, and have therefore, been employed to determine (spontaneous) metal dissociation rate constants. , It is important to point out in this connection, however, that some reported observations (such as the dependence of the rate of inactivation on the concentration of EDTA, or the increased protection against inactivation by higher substrate concentrations) have challenged the longstanding assumption that EDTA follows a strictly dissociative mechanism. …”
mentioning
confidence: 99%